Impact of corticotropin-releasing hormone on gastrointestinal motility and adrenocorticotropic hormone in normal controls and patients with irritable bowel syndrome. Issue 6 (1st June 1998) - Fukudo, S; Nomura, T; Hongo, M
Abstract : Background —Corticotropin-releasing hormone (CRH) plays a key role in modulating intestinal motility in stressed animals. Aims —To evaluate the effect of CRH on intestinal motility in humans and to determine whether patients with irritable bowel syndrome (IBS) have an exaggerated response to CRH. Subjects —Ten IBS patients diagnosed by Rome criteria and 10 healthy controls. Methods —CRH (2 μg/kg) was intravenously administered during duodenal and colonic manometry and plasma adrenocorticotropic hormone (ACTH) was measured by radioimmunoassay. Results —CRH induced motility of the descending colon in both groups (p<0.001) and induced greater motility indexes in IBS patients than in controls (p<0.05). CRH produced duodenal phase III motor activity in 80% of the subjects and duodenal dysmotility in 40% of IBS patients. Abdominal symptoms evoked by CRH in IBS patients lasted significantly longer than those in controls (p<0.05). CRH induced significant increases in plasma ACTH levels in both groups (p<0.001) and produced significantly higher plasma ACTH levels in IBS patients than in controls (p<0.001). Conclusion —Human intestinal motility is probably modulated by exogenous CRH. The brain-gut in IBS patients may have an exaggerated response to CRH.